Development of the System of Club Education in Ukraine in 1960-1980-s - Dmytro Ovsiienko (Pedagogical Discourse, 2014)
This article examines the problem of formation of human resources in clubs of Ukraine in 1960-1980 's. Attention is drawn to the objective and subjective reasons that lead to the decline in the prestige of the profession of club worker in the independent Ukraine. The problems of the formation of human resources in cultural institutions in the Soviet times. A comparative analysis of the cultural sector in Ukraine in 1960-1980 -s and the period of Ukraine’s independence (from 1990 to 2012). The differences between the development of cultural and educational activities at the time of stay in Ukraine Soviet Union and since the independence are taken into account. The problems of education in Ukraine club in Soviet and post-Soviet period are cleared up. Existing proposals of optimization of club affairs by deideologization latter focus on solving the problems of Ukrainian national revival of cultural traditions and spiritual development of the younger generation. The attention is focused on the fact that the content and level of work of clubs depends on the professionalism of club staff. On the basis of summarizing it is determined that reduce of cultural and educational activities in Ukraine in the post-socialist period due to the fact that the authorities today do not give due importance to the profession of club employee up to the point as it was investigated for 60-80-s years of the previous century.